Black bean peptides inhibit glucose uptake in Caco-2 adenocarcinoma cells by blocking the expression and translocation pathway of glucose transporters - Luis Mojica; Diego A. Luna-Vital; Elvira Gonzalez de Mejia (Toxicology Reports, 2018)
The objective was to evaluate the effect of black bean protein fraction (PFRA), and its derived peptides on glucose uptake, SGLT1 and GLUT2 expression and translocation on Caco-2 cells. The effect of treatments was evaluated on glucose uptake, protein expression and localization and gene expression on Caco-2 cells. PFRA (10 mg/mL) lowered glucose uptake from 27.4% after 30 min to 33.9% after 180 min of treatment compared to untreated control (p < 0.05). All treatments lowered GLUT2 expression after 30 min of treatment compared to untreated control (31.4 to 48.6%, p < 0.05). Similarly, after 24 h of treatment, GLUT2 was decreased in all treatments (23.5% to 48.9%) (p < 0.05). SGLT1 protein expression decreased 18.3% for LSVSVL (100 μM) to 45.1% for PFRA (10 mg/mL) after 24 h. Immunofluorescence microscopy showed a decrease in expression and membrane translocation of GLUT2 and SGLT1 for all treatments compared to untreated control (p < 0.05). Relative gene expression of SLC2A2 (GLUT2) and SLC5A1 (SGLT1) was downregulated significantly up to two-fold change compared to the untreated control after 24 h treatment. Black bean protein fractions are an inexpensive, functional ingredient with significant biological potential to reduce glucose uptake and could be used as an adjuvant in the treatment of colorectal cancer. Keywords: Black bean protein fraction, Colorectal cancer, Glucose uptake, GLUT2, SGLT1